No human respiratory syncytial virus but SARS‐CoV‐2 found in children under 5 years old referred to Children Medical Center in 2021, Tehran, Iran. Issue 7 (8th March 2022) - Letafati, Arash; Aghamirmohammadali, Fahimeh Sadat; Rahimi‐Foroushani, Abbas; Hasani, Seyed Abbas; Mokhtari‐Azad, Talat; Yavarian, Jila
Abstract: Acute respiratory infections (ARIs) are one of the leading causes of illness and death among community members worldwide. Viral infections are the most common agents estimated to be involved in these patients. This study aimed to investigate the prevalence of human respiratory syncytial virus (hRSV) and severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) among children with ARIs. This study evaluated the presence of SARS‐CoV‐2 and hRSV in 168 throat and nasopharyngeal swab samples using real‐time RT‐PCR. All samples were collected from children under 5 years old with ARIs who attended Children's Medical Center, Tehran, Iran, and sent to the Iranian National Influenza Center with appropriate conditions in 2021. Chi‐square and Fisher's exact tests were used for comparison of the data of the prevalence of hRSV and SARS‐CoV‐2 infections among children. Of 168 patients examined, 95 (57%) were male and 73 (43%) female. Out of them, 47 (28%) cases were younger than 1 year old and 121 cases (72%) were 1–5 years old. The most common clinical manifestations of patients were cough (78%), nausea (31%), diarrhea (27%), and fever (18%). Among 168 patients, no hRSV was detected, while the SARS‐CoV‐2 genome was identified in 16 (9.5%) patients. Among 16 positive cases of SARS‐CoV‐2, 8 (50%) were under 1 year old and 8 positive cases were 1–5 years old. This study was performed at cold months of the year but due to the coronavirus disease 2019 pandemic and adherence to health protocols, school closures, and virtual classes, no cases of hRSV infections were identified.